Analysis of Unemployment Patterns in Indonesia Using K-Means Clustering and Identification of Dominant Factors Using Random Forest - Yuliana; Rima Fazri Ramadhania; Asep Abdul Latip; Muhammad Farhan Harahapa (Jurnal Inotera, 2026)
The disparity in the unemployment rate between provinces in Indonesia, exacerbated by the COVID-19 pandemic, is the main focus of this study. This study aims to (1) map the grouping of unemployment patterns in 34 provinces based on the Open Unemployment Rate (TPT) time series data for the 2020-2024 period, and (2) analyze the most significant socio-economic determinants of the formation of these patterns. Applying a two-stage methodology, cluster analysis using K-Means—validated through the Elbow Method and Silhouette Score of 0.456—succeeded in classifying the provinces into four different groups. The two prominent clusters identified were "Cluster 2: Pandemic Shock Pattern" (e.g., DKI Jakarta, West Java) which showed a surge in TPT above 10%, and "Cluster 3: Resilient Pattern" (e.g., Bali, DIY) which showed the lowest TPT rate and fastest recovery. Furthermore, the Random Forest Classifier analysis identified a hierarchy of determining factors, with the 2024 Average School Length (RLS) as the strongest predictor, followed by the 2024 Provincial Minimum Wage (UMP) and the 2024 GDP. These findings underline that the quality of human capital (education) is a more crucial factor than economic output (GDP) in shaping the resilience of the labor market. The study concludes the need for differentiated and cluster-specific unemployment policy interventions, rejecting a nationally uniform approach.